REHABILITATION OF DEVASTATED PEAT LANDS AND ESTABLISHMENT OF SUSTAINABLE AGRO-SYSTEMS THROUGH BUFFER ZONE PLANNING IN CENTRAL KALIMANTAN - Osaki, Mitsuru; Wijaya, Hanny; Simbolon, Herwint (BERITA BIOLOGI, 2000)
-